Exact vortex solutions of the Navier–Stokes equations with axisymmetric strain and suction or injection - CRAIK, ALEX D. D. (Journal of fluid mechanics, 2009)
New solutions of the Navier–Stokes equations are presented for axisymmetric vortex flows subject to strain and to suction or injection. Those expressible in simple separable or similarity form are emphasized. These exhibit the competing roles of diffusion, advection and vortex stretching.